The Effect Of The Use Of Outboard Motors On Efforts To Maintain Family Economic Management - Kristian Cahyandi; Andi Hendrawan; Ningrum Astriawati (Cita Konsultindo Research Center, 2023)
Kampung Laut is a sub-district located in Cilacap Povinsi Regency, Central Java, with the majority of the population working as traditional fishing fishermen. People in Kampung Laut face problems in the form of narrowing fishing areas as a place to make their daily living, which is caused by siltation through the sedimentation process along the Segara Anakan Lagoon. The purpose of this study is to determine whether or not there is a relationship between the influence of the use of engines (outboard motors) on Kampung Laut fishing boats to maintain the family economy of management in the Cilacap Regency area. This research uses a descriptive research method with a qualitative approach. The study was conducted through a SWOT analysis, with results showing the need for management of the use of engines (outboard motors) on Kampung Laut fishing boats to increase income through efforts to expand the fishing area to the high seas. The results of the study also stated that there is a need for assistance from the Government to assist in obtaining access to funding through financial institutions.